Impact of a computerized physician order entry system on medication safety in pediatrics-The AVOID study - Wimmer, Stefan; Toni, Irmgard; Botzenhardt, Sebastian; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmacology Research and Perspectives, 2023)
BACKGROUND: One of the most critical steps in the medication process on pediatric wards is the medical prescription. This study aims to investigate the impact of a computerized physician order entry (CPOE) system on Adverse Drug Events (ADEs) and potentially harmful ADEs (pot ADEs) in comparison with paper-based documentation in a general pediatric ward at a German University hospital. METHODS: A prospective pre-post study was conducted. All patients aged 17 years or younger were observed during the study periods (5 months pre- and postimplementation). Issues Regarding Medication (IRM) were identified by intensive chart review. Events were assessed regarding causality (WHO), severity (WHO; Dean & Barber for MEs), and preventability (Shumock) and classified into (pot) ADEs, (pot) Medication errors (ME), Adverse drug Reactions (ADR), and Other incidents (OI) accordingly. RESULTS: Total of 333 patients with medication were included in the paper-based prescribing cohort (phase I) and 320 patients with medication in the electronic prescribing cohort (phase II). In each cohort, patients received a median number of four different drugs (IQR 5 and IQR 4). A total of 3966 IRM was observed. During the hospitalization, 2.7% (n = 9) patients in phase I and 2.8% (n = 9) in phase II experienced an ADE. Potentially harmful MEs were less often observed in the cohort with electronic prescribing (n = 228 vs. n = 562). The mean number per patient significantly decreased from 1.69 to 0.71 (p < .01). CONCLUSION: The implementation of a CPOE system resulted in a reduction of issues regarding medication, particularly MEs with the potential to harm patients decreased significantly.
CRIS-Team Scopus Importer:2023-06-02
Keywords: adverse drug event; adverse drug reaction; computerized physician order entry; electronic prescribing; medication error; medication safety; pediatrics